Socialization of the Construction of Waste Water Canals For Fishermen - Putri IS. Samad; Wahrini, Retyana; Supriadi; ganggang canggi arnanto (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
Water is a basic need for life, especially for humans who always need water throughout their lives. The human body consists mostly of water. Household waste is waste that comes from kitchens, bathrooms, laundry, household industrial waste and human waste. This community service aims to improve sanitation through the construction of closed wastewater channels and safe reservoirs, as well as providing education to the local fishing community. The methods used include initial surveys, planning and design, training and counseling, physical development, as well as evaluation and monitoring. The construction of the channel was carried out using concrete and septic tanks, accompanied by technical training for the community. The results show an increase in community knowledge and skills in wastewater management. Through the implementation of Community Service (PKM) activities, it can be concluded that efforts to improve fishermen's skills in making household waste channels is a significant step in improving sanitation and public health. This activity has produced several results that can be measured quantitatively, such as increasing partner knowledge by 80%. This figure is based on the results of pre-test and post-test evaluations carried out before and after the training, where participants' knowledge of drainage construction techniques and the importance of sanitation increased significantly